2017
DOI: 10.1177/0884533617712226
|View full text |Cite
|
Sign up to set email alerts
|

Micronutrient Deficiencies After Bariatric Surgery: An Emphasis on Vitamins and Trace Minerals

Abstract: Obesity has become a worldwide epidemic with a disproportionate increase in grade III obesity. Bariatric surgery offers an attractive option for sustained weight loss compared with traditional methods such as exercise and diet. Micronutrient deficiencies are common and clinically significant after bariatric surgery. These deficiencies are related to a combination of patient and surgical variables. A thorough understanding of specific micronutrient deficiencies is necessary for early recognition and optimal man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 68 publications
(119 reference statements)
1
41
0
2
Order By: Relevance
“…The underlying variables associated to postoperative vitamin and mineral deficiencies are both surgery-and patient-related ( Figure 3 Micronutrient deficiencies are frequently reported after RYGB and VSG [9,51,96,97], with an incidence as great as 50% in mid-and long-term follow-ups [86]. The underlying variables associated to postoperative vitamin and mineral deficiencies are both surgery-and patient-related ( Figure 3) [98].…”
Section: Pathogenesis Of Micronutrient Deficiencies After Bsmentioning
confidence: 99%
“…The underlying variables associated to postoperative vitamin and mineral deficiencies are both surgery-and patient-related ( Figure 3 Micronutrient deficiencies are frequently reported after RYGB and VSG [9,51,96,97], with an incidence as great as 50% in mid-and long-term follow-ups [86]. The underlying variables associated to postoperative vitamin and mineral deficiencies are both surgery-and patient-related ( Figure 3) [98].…”
Section: Pathogenesis Of Micronutrient Deficiencies After Bsmentioning
confidence: 99%
“…One of the most important, prevalent, and consequential nutritional concerns is alterations in iron metabolism primarily due to the surgery and to a variable extent due to certain unique characteristics of patients with severe obesity. Only recently recognized and not well studied is the increasing evidence for the long‐term development of severe iron deficiency often leading to modest to severe anaemia resulting from metabolic surgery …”
Section: Introductionmentioning
confidence: 99%
“…Morbid Obesity also is related to menstrual irregularities, complexities in pregnancy, hirsutism, and psychosocial disorders (23,24). One study which is conducted of 527,000 men and women in the age of 50 -71 years old, those with a BMI of more than 40 kg/m 2 had the higher risk of mortality (25). More than one billion adults are affected by obesity in world-wide.…”
Section: Morbid Obesitymentioning
confidence: 99%
“…Low physical activity and increment in the energy dense foods consumption may be an important indicator in obesity (28). Unfortunately, despite effort of morbid obese patients, ambulatory treatments such as exercise, diet, and nutrient counseling do not provided sustained weight loss (25), and it is found that Bariatric surgery provides the highest level of effectiveness in obtaining sustained weight loss among seriously obese patients, as compared with that of all other treatments (29).…”
Section: Morbid Obesitymentioning
confidence: 99%
See 1 more Smart Citation